Evidence for the stabilization of FeN4 sites by Pt particles during acidic oxygen reduction - Nicolas A. Ishiki; Keyla Teixeira Santos; Nicolas Bibent; Kavita Kumar; Ina Reichmann; Yu-Ping Ku; Tristan Asset; Laetitia Dubau; Michel Mermoux; Hongxin Ge; Sandrine Berthon-Fabry; Viktoriia A. Saveleva; et al. (Nature Communications)
Abstract While Fe–N–C materials have shown promising initial oxygen reduction reaction (ORR) activity, they lack durability in acidic medium. Key degradation mechanisms include FeN4 site demetallation and deactivation by reactive oxygen species. Here we show for mainstream Fe–N–Cs that adding 1 wt.% Pt nanoparticles via a soft polyol method results in well-defined and stable Pt/Fe–N–C hybrids. The Pt addition strongly reduces the H2O2 production and Fe leaching rate during ORR, while post mortem Mössbauer spectroscopy reveals that the highly active but unstable Fe(III)N4 site is partially stabilized. The similar H2O2 electroreduction activity of Pt/Fe–N–C and Fe–N–C and other analyses point toward a long-distance electronic effect of Pt nanoparticles in stabilizing FeN4 sites. Computational chemistry reveals that spin polarization of distant Pt atoms mitigates the structural changes of FeN4 sites upon adsorption of oxygenated species atop Fe, especially in high-spin state.